2022
DOI: 10.1021/acscatal.2c03743
|View full text |Cite
|
Sign up to set email alerts
|

The Road Less Traveled: Unconventional Site Selectivity in Palladium-Catalyzed Cross-Couplings of Dihalogenated N-Heteroarenes

Abstract: The vast majority (≥90%) of literature reports agree on the regiochemical outcomes of Pd-catalyzed cross-coupling reactions for most classes of dihalogenated N-heteroarenes. Despite a well-established mechanistic rationale for typical selectivity, several examples reveal that changes to the catalyst can switch site selectivity, leading to the unconventional product. In this Perspective, we survey these unusual cases in which divergent selectivity is controlled by ligands or catalyst speciation. In some cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…The optimized conditions also lead to exclusive cross‐coupling at the C5 triflate of 2‐chloro‐5‐trifloylpyridine ( 11 ). This result is notable because products like 11 are difficult to access from 2,5‐dichloropyridine: all reported Suzuki couplings of the dichlorinated substrate in the presence of ligands lead to selective reaction at C2 [14,15] . Aryl chlorides are profoundly inert under the optimized ligand‐free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The optimized conditions also lead to exclusive cross‐coupling at the C5 triflate of 2‐chloro‐5‐trifloylpyridine ( 11 ). This result is notable because products like 11 are difficult to access from 2,5‐dichloropyridine: all reported Suzuki couplings of the dichlorinated substrate in the presence of ligands lead to selective reaction at C2 [14,15] . Aryl chlorides are profoundly inert under the optimized ligand‐free conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of additional phosphine ligands on the reaction has been probed systematically. 13 We found that the reactions have been restrained by adding additional phosphines, even PPh 3 ligands, under the reaction condition in entry 5 (entry 7, see Section S29 in the ESI † for further details). We speculate that the trace decomposition of the metalla-aromatic substrates would provide sufficient PPh 3 ligands to form catalytically active Pd species.…”
Section: Resultsmentioning
confidence: 99%
“…Site-selective functionalization of molecules that contain multiple reactive sites remains a significant challenge in organic synthesis. Along with this challenge comes the opportunity that achieving site-selective functionalization could enable synthesis of a variety of molecules from a small subset of starting materials. While selective functionalization of electrophiles that contain two reactive sites has been significantly developed (e.g., 1,2 vs 1,4 addition to α,β-unsaturated carbonyl compounds), development of methods to functionalize extended π systems has lagged.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pyridinium salts are multident electrophiles that, in the presence of nucleophiles, can undergo (1,2), (1,4), or (1,6) addition to afford the corresponding dihydropyridines (DHPs). 8−31 These scaffolds are useful intermediates for the preparation of nonaromatic nitrogen heterocycles (Figure 1A).…”
Section: ■ Introductionmentioning
confidence: 99%